Genetic diversity among Plasmodium vivax isolates along the Thai–Myanmar border of Thailand. (December 2016) - Maneerattanasak, Sarunya; Gosi, Panita; Krudsood, Srivicha; Tongshoob, Jarinee; Lanteri, Charlotte; Snounou, Georges; Khusmith, Srisin
Abstract Background Knowledge of the population genetics and transmission dynamics ofPlasmodium vivax is crucial in predicting the emergence of drug resistance, relapse pattern and novel parasite phenotypes, all of which are relevant to the control of vivax infections. The aim of this study was to analyse changes in the genetic diversity ofP. vivax genes from field isolates collected at different times along the Thai–Myanmar border. Methods Two hundred and fifty-fourP. vivax isolates collected during two periods 10 years apart along the Thai–Myanmar border were analysed. The parasites were genotyped by nested-PCR and PCR–RFLP targeting selected polymorphic loci ofPvmsp1, Pvmsp3α andPvcsp genes. Results The total number of distinguishable allelic variants observed forPvcsp, Pvmsp1, andPvmsp3α was 17, 7 and 3, respectively. High genetic diversity was observed forPvcsp (H E  = 0.846) andPvmsp1 (H E  = 0.709). Of the 254 isolates, 4.3 and 14.6 % harboured mixedPvmsp1 andPvcsp genotypes with a mean multiplicity of infection (MOI) of 1.06 and 1.15, respectively. The overall frequency of multiple genotypes was 16.9 %. When the frequencies of allelic variants of each gene during the two distinct periods were analysed, significant differences were noted forPvmsp1 (P  = 0.018) and thePvcsp (P  = 0.033) allelic variants. Conclusion Despite the low malaria transmission levels in Thailand, P. vivax population exhibit a relatively high degree of genetic diversity along the Thai–Myanmar border of Thailand, in particular forPvmsp1 andPvcsp, with indication of geographic and temporal variation in frequencies for some variants. These results are of relevance to monitoring the emergence of drug resistance and to the elaboration of measures to control vivax malaria.